"Since I Am From Where I Am From": How Rural and Urban First-Generation College Students Differentially Use Social Capital to Choose a College Major - Lillian R. Sims; Joseph J. Ferrare (Journal of Research in Rural Education, 2021)
By definition, first-generation college (FGC) students share similar levels of parental education, and they often receive support on college campuses as though they represent a homogenous group. However, FGC students come from a wide variety of backgrounds that may necessitate different forms of support. This article takes a step toward exploring this variation by examining how rural and urban FGC freshmen differentially use their social networks to help them choose college majors and career pathways. The case study uses longitudinal interviews with 18 rural FGCs and 15 urban FGCs to tease apart the ways in which rural and urban places create distinct challenges and opportunities that affect the transition to college. The analysis also examines the ways in which race interacts with place to further shape these processes. Most notably, urban students benefited from career exploration opportunities available in their cities and high schools and were preconditioned to see their home communities as sources of social capital, while rural students relied heavily upon fewer hometown mentors but also understood the urgency of forming new ties in college and ultimately bridged more successfully into the collegiate sphere. In addition, with potential implications for student affairs professionals, administrators, faculty, and others seeking to support and mentor FGC students, rural students in particular rejected the FGC label and associated more strongly with their geographic background. Finally, while Black and White students from rural and urban areas often pursued similar college majors, their experiences along these trajectories often diverged in meaningful ways.